2015
DOI: 10.1093/eurpub/ckv122
|View full text |Cite
|
Sign up to set email alerts
|

The impact of electronic health records on healthcare quality: a systematic review and meta-analysis

Abstract: EHR system, when properly implemented, can improve the quality of healthcare, increasing time efficiency and guideline adherence and reducing medication errors and ADEs. Strategies for EHR implementation should be therefore recommended and promoted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
179
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(191 citation statements)
references
References 15 publications
3
179
0
9
Order By: Relevance
“…A study by Gommans et al in New Zealand has shown that rates of identification compliance among medical staff could be improved from 10% to 81% when the medication chart was changed to a single page requiring a single sticker and name . Several public and private hospitals within Queensland, Australia, have recently implemented the digitalisation of hospitals, which is regarded as a measure to improve medication safety . With digitalisation of prescribing, certain aspects of the NIMC audit tool, such as legibility and presence of patient ID stickers, will become redundant.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Gommans et al in New Zealand has shown that rates of identification compliance among medical staff could be improved from 10% to 81% when the medication chart was changed to a single page requiring a single sticker and name . Several public and private hospitals within Queensland, Australia, have recently implemented the digitalisation of hospitals, which is regarded as a measure to improve medication safety . With digitalisation of prescribing, certain aspects of the NIMC audit tool, such as legibility and presence of patient ID stickers, will become redundant.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis found that EHRs have a positive effect on quality of care. EHR use was associated with increased guideline adherence (RR 1.33, 95% CI 1.01-1.76), a lower number of medication errors (RR 0.46, 95% CI 0.38-0.55), and fewer adverse drug events (RR 0.66, 95% CI 0.44-0.99) [25]. Our current approach does not capture the clinical detail that contributes to a medical decision at the bedside.…”
Section: Discussionmentioning
confidence: 99%
“…Boland et al (2013) carried out a systematic review and meta-analysis to assess the cost-effectiveness of Chronic Obstructive Pulmonary Disease Disease Management (COPD-DM) programs in Netherlands, suggesting that COPD-DM programs have favorable effects on both health outcomes and costs, but there was considerable heterogeneity depending on patient, intervention, and study-characteristics. Campanella et al (2015) applied meta-analysis to assess the impact of electronic health record (EHR) on healthcare quality and the impact of Public Reporting on clinical outcomes (Campanella et al 2016). Gallet and Doucouliagos (2017) applied meta-regression analysis (MRA), and examine the healthcare spending elasticity for the mortality rate and the spending elasticity for life expectancy.…”
Section: Why Meta-analysis Is Used To Re-examine the Impact Of Healthmentioning
confidence: 99%